ANALISIS ALIH KODE DAN CAMPUR KODE PADA FILM “SANG PRAWIRA EPISODE I DAN EPISODE II” KARYA ONET ADITHIA RIZLAN - Wanda Wanda; Ati Rosmiati (Tuwah Pande: Jurnal Ilmu Pendidikan dan Pengajaran, 2022)
This study of code switching and code mixing analysis in the film "Sang Prawira Episode I and Episode II" by Onet Adithia Rizlan aims to determine code switching and code mixing sentences based on the types in the film "Sang Prawira Episode I and Episode II". The benefit of this research is to be able to add insight about code switching and code mixing in the film for anyone who reads it. This research uses descriptive qualitative methods, meaning that descriptive qualitative methods are methods that describe and describe and to produce data in the form of sentences to understand sentences that state code switching and code mixing. The data analysis technique used in this research is the listening technique and the note-taking technique. Based on the results of the study, it can be concluded that the number of code switching that occurs in Episode I is 5 sentences (conversational code switching 3, situational code switching is 2), and in Episode II it is 6 sentences (conversational code switching 5, metaporical code switching 1 ). So the total code switching that occurred in Episode I and Episode II was 11 code switching sentences. Meanwhile, the code mixing that occurred in the Episode I film was 48 sentences (mixed code level 45 words, mixed code level phrase 2, mixed code level clause 1), and in Episode II there were 22 sentences (mixed code level 16 words, mixed Phrase level code is 6). So the total code-mixing that occurred in Episode I and Episode II was 70 code-mixing sentences.